Brown mustard (Brassica juncea czern) processing by-products: Effects of mustard meal xenobiotics on the productive performance and antioxidant system of laying hens - Ionov, Igor A; Gaviley, Olena V; Fotina, Tetiana I; Griffin, Darren K; Romanov, Michael N (Asian Journal of Agriculture and Rural Development, 2026)
Brown mustard (Brassica juncea Czern) is a widely cultivated crop in Asia and throughout the world. Mustard meal, a by-product of mustard oil extraction, has potential as a feed ingredient for poultry. There are concerns, however, that it contains xenobiotic compounds such as mustard oils that may affect metabolism and productivity. This study evaluated the impact of including 5% mustard meal in layer diets on egg production, antioxidant status, and vitamin content, identifying effective feed additives for metabolic normalization. A total of 500 Rhode Island White laying hens (150 days old) were divided randomly into five groups. The control group received a standard diet, while experimental groups received diets containing 5% mustard meal with different supplements: vermiculite sorbent, santoquin with vitamin E, or methionine with glucose. The incorporation of mustard meal retarded egg production during the first two weeks, but performance stabilized thereafter. Oxidative stress intensity was significantly higher in hens fed mustard meal compared to the control. All tested additives enhanced the antioxidant defense system, reflected in reduced malondialdehyde concentrations in blood serum. The antioxidant santoquin proved to be the most effective protector against mustard oil-induced oxidative stress. Supplementation with santoquin and vitamin E or methionine with glucose increased yolk carotenoid and tocopherol levels without affecting retinol or vitamin B2 concentrations. In general, inclusion of mustard meal in the diet at a level of 5% may be feasible in combination with suitable protective additives, in particular santoquin+vitamin E, to ensure both productive stability and physiological resistance in laying hens.